Perancangan dan Pengembangan E Brosur dan E Catalog Pada First Hook Coffee - heru Wijayanto Aripradono; Winson Ng (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This community service program has the aim of increasing sales, brand awareness and adding new consumers by using e-catalogs and e-brochures. This E-Catalog and E-Brochure contain beverage products sold by First Hook Coffee. Partners in community service are First Hook Coffee which is a Coffee Shop business located in the Nusa Jaya housing block F no 11, Sungai Panas, Batam. The method used in this activity is observation and interviews. The application used by the author to create E-catalogs and E-brochures is Adobe Photoshop CC 2019. The implementation results show an increase in new marketing reach, an increase in profit and an increase in new consumers